Penggunaan Model Pembelajaran Tipe Cooperative Script terhadap Hasil Belajar Siswa pada Mengidentifikasi Persyaratan Pemasangan Ubin Lantai dan Dinding, Batu Alam dan Batu Buatan di Kelas XII KGSP. SMKN-1 Palangka Raya Tahun Ajaran 2021/2022” - Whendy Trissan; Ni Putu Diah Agustin Permanasuri; Krisno Krisno (Journal on Education, 2023)
Education is an effort to prepare human resources who have expertise and skills according to the demands of nation building, the quality of a nation is very effective in the use of educational factors. The realization of a quality society is the responsibility of education, especially in preparing students who are creative, independent, and professional in their respective fields. This study discusses the use of the cooperative script model on student learning outcomes in the material to identify the requirements for installing floor and wall tiles, natural stone and artificial stone. This study aims to determine student learning outcomes on the material to identify the requirements for installing floor and wall tiles, natural stone and artificial stone. This study uses a quantitative approach. This type of research is a true experimental research design with a post-test only control design. The population in this study were all students of class XII KGSP, totaling 28 students. As for the sample in this study used random sampling. The research conducted interviews, observations, documentation and tests to obtain data. The results of the study stated that the learning outcomes of class XII KGSP students who used the cooperative script learning model were in the good category with an average score of 70 and the learning outcomes of students who did not use the cooperative script model were in the sufficient or low category with an average score of 49.